Modeling Professionally Applied Physical Training of Female Students at the School of Pre-School Education through Rhythmic Gymnastics - Т. М. Кравчук; Н. М. Санжарова; Ю. В. Голенкова (OVS LLC, 2015)
The paper offers a model of professionally applied physical training of female students of the School of Pre-School Education through rhythmic gymnastics. The study proves that rhythmic gymnastics exercises have health-improving, developmental, educational and aesthetic potential, which makes them an effective means of professionally applied physical training of future teachers at pre-school institutions. The offers a set of rhythmic gymnastics exercises selected specifically for professionally applied physical training of female students at the School of Pre-School Education, and a model designed to implement such training during the period of studies at the higher educational institution.